Legal Politics in Food Estate Program for Community Welfare - Mutia Evi Kristhy; Andri Andri; Fidelis Harefa (Budapest International Research and Critics University, 2022)
The need for food is a basic human need that must be met. The Food Estate is an idea for food security implemented through agriculture or plantations. There are various aspects of food security interrelated, including self-reliance, sovereignty, and food security. This study aims to analyze the food estate of view of legal politics. The research method used is a qualitative research method using a normative legal approach. The study results indicate that the Food estate has an unfair impact on the community due to the unavailability of opportunities given to local communities in making decisions. Therefore, in food estate necessary to pay attention to various aspects and understand the characteristics of the land and local communities.